Effect of Container Orientation on Melt Fraction and Use of PCM in Enhancing Night Temperature in a Prototype Solar Kiln - Kumar, Shailendra; Kishan Kumar, V. S. (Indian Forester, 2017)
Effect of container orientation on melt fraction of a commercial Phase Change Material (PCM) filled in commercial High Density Poly-Ethylene (HDPE) containers placed in a prototype solar kiln was studied. The melt fraction was found to be much higher in horizontally placed containers compared to vertically oriented ones. In order to understand the effect of stored thermal energy in PCM, the kiln was first tested in empty condition by closing all doors and vents until kiln temperature fell to 40° C by 22:00 hrs. It was again tested by placing 80 kg of a commercial phase change material filled in 25 HDPE containers placed horizontally inside the kiln. A temperature of 65°C was maintained inside the kiln till 17:00 hrs by suitable venting. It was found that the solar kiln was able to maintain temperatures above 40°C until 03:00 hrs with the help of PCM filled containers placed horizontally which was 6 hrs more than that of without thermal storage.